PATHOPHYSIOLOGICAL PATTERNS OF REPARATIVE PROCESSES UNDER DIFFERENT MODES OF LASER TISSUE TREATMENT - Sadikov, Rasul; Sadikov, Rustam; Bobokulov, Khakim (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The aim of the study was to investigate the patterns of wound healing and reparative processes under different modes of laser tissue treatment in an experimental setting.